(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this paper, the dynamics of scavenger species in a web food model incorporating time delay and prey harvesting is formulated mathematically. Boundednes of all solutions of the model carried out. The existence as well as stability analysis of all possible positive equilibrium points are discussed. Also, we proved that under certain time delay, our model exhibits a subcritical Hopfbifurcation. Furthermore, to confirm our analytical finding, we studied numerical simulation for the model.